PHYSICO-CHEMICAL, NUTRITIONAL AND SENSORY QUALITIES OF CASSAVA-WHEAT SEMOLINA MACARONI NOODLES (2012)
Noodles are popular foods worldwide because of their unique sensory properties, shelf stability, simplicity of preparation and low costs. The demand for these products traditionally made from Durum-Wheat Semolina (DWS) has increased tremendously; hence, the need to utilize locally available tropical root crops in the development of such products. This study was undertaken to evaluate the potentials of using cassava – wheat blend in the production of macaroni noodles. High Quality Cassava Starch (HQCS) from improved low-cyanide cassava variety (TMS 30572), was mixed with DWS in pre-determined ratios to produce flours containing 0, 20, 30, 50, 70 and 100% HQCS. These were analysed for chemical composition (proximate, sugar, cyanide) and physico-chemical properties (pasting, amylose, water binding capacity, starch damage, α-amylase activity, dough mixing stability) by AOAC and American Association of Cereal Chemists’ approved methods. Macaroni noodles were produced from the flour samples mixed with 5.0% soya flour. Effects of the six levels of HQCS inclusion and variation in hydration levels (45.0, 50.0 and 55.0%) on dough and macaroni were determined using a randomized complete block factorial design. Macaroni composition (proximate, energy, sugar, mineral profile), physico-chemical properties (pasting, amylose, cooking losses), microbiological quality and sensory characteristics (preference and difference tests) of the noodles were also evaluated using standard procedures. Data were analysed using propriety software. Blends of HQCS and DWS had moisture, protein, fat and ash contents ranging from 10.4-11.6%, 0.8-12.1%, 1.0-4.4% and 0.1-0.8%, respectively. Protein content of flour blends and dough mixing stability decreased with increasing levels of HQCS. Cyanide levels in all the flour samples were less than 0.1 ppm and α-amylase activity was greater than 200. The DWS and HQCS samples had similar pasting temperatures (50.2oC). Other pasting properties of flour samples including peak viscosity, holding strength, breakdown and final viscosities increased with increasing levels of HQCS. Developed macaroni noodles had 5.3-14.2% protein, 3.8-5.1% fat, 1.5-2.1% ash at 0 to 80% DWS inclusion; and also 70.3-82.8% carbohydrate and 383.9-386.4 kcal/100g energy between 20 and 100% levels of HQCS inclusion. Addition of soya flour to the blends during macaroni production increased protein content of the noodles. Iron and calcium contents increased from 28.9 to 72.0 and 627.5 to 819.1 mg/kg, respectively as HQCS inclusion increased from 20 to 70%. Microbial load (6.83x103 - 3.33x104 cfu/g) was within acceptable limits and no organism of public health significance was detected. The inclusion of HQCS reduced cooking time from 11 to 7 min, but increased solid and soluble cooking losses. The correlation between final pasting viscosity and total cooking loss was significant (r = 0.9; p<0.05). Inclusion of HQCS, hydration levels and their interactions, had significant effect (p<0.01) on macaroni cooked weight, water absorption index, swelling volume, solid and soluble losses. The acceptable macaroni were those containing 30 and 50% HQCS, beyond which cooking and sensory properties were adversely affected. New macaroni noodles with acceptable sensory, physico-chemical, nutritional and microbiological qualities were developed from cassava–wheat blends. Calcium, iron and energy contents of macaroni were improved, thus enhancing cassava utilization.